Incorporating the diagnosis and management of female genital schistosomiasis in primary healthcare in Liberia: a mixed methods pilot study. (24th March 2023) - Nganda, Motto; Bettee, Anthony K; Kollie, Karsor; Nallo, Gartee E; Juabeh, Matthews; Wright, Abednego; Thomson, Rachael; Dean, Laura
Abstract: Background: Liberia's national neglected tropical disease (NTD) master plan 2016–2020 adopted the need for integrated approaches to tackle the threat of specific NTDs including schistosomiasis. Female genital schistosomiasis (FGS) affects up to 75% of women and girls living in schistosomiasis-endemic areas. Liberia's Bong and Nimba counties are endemic for schistosomiasis. The communities affected are poor and dependent on primary healthcare services. Incorporating the diagnosis and treatment of FGS within primary healthcare is a critical step in the control and elimination of schistosomiasis in Liberia. The Calling Time for Neglected Tropical Diseases (COUNTDOWN) research programme partnership included the Liberia Ministry of Health NTD programme. Together, partners designed this study to co-develop, pilot and evaluate a primary healthcare package for clinical diagnosis and management of FGS in Liberia. Methods: Mixed methods were applied to assess the intervention outcomes and process. Quantitative descriptive analysis of routine health facility (secondary) data was used to characterise women and girls diagnosed and treated for FGS. Qualitative rapid analysis of meeting reports and training observations, thematic framework analysis of in-depth interviews with women and girls and key-informant interviews with health system actors were used to establish the success and sustainability of intervention components. Results: In 6 months, 258 women and girls were diagnosed and treated for FGS within routine service delivery across six primary health facilities. Diagnosis and treatment were completed by health facility staff who had been trained in the FGS intervention developed within this study. Some women diagnosed and treated had symptom relief or were optimistic about the intervention due to improved diagnostic and treatment communication by health workers. Health workers and stakeholders were satisfied with the care package and attributed intervention success to the all-inclusive approach to intervention design and development; cascaded training of all cadres of the health system; and the locally driven intervention rollout, which promoted local ownership and uptake of intervention components. Conclusion: This study demonstrates the possibility of using a clinical care package to diagnose women and girls suspected of FGS, including the provision of treatment using praziquantel when it is made available at primary healthcare facilities.